Kebijakan Swasembada Gula di Indonesia - Surono, Sulastri (UI Scholars Hub, 2006)
Indonesia was the 2nd largest exporter of sugar after Cuba in 1930 but we became the 2nd largest importer of sugar on 1999. The goverrzment launched protection and promotion policy to save the sugar industry since 2000. Protection policy is practiced by imposing some import tariffs while government promoted Increase in Acceleration of National Sugar Production Program since 2002. The goal is to reach sugar self sufficiency for household consumption on 2007 and for both household and industry consumption on 2009. There are some basic things which notes the importance of sugar self sufficiency in Indonesia. First, maintain food sustainability. Second, to maximize sugar industry capacity that is quite big. Third, to develop domestic sugar industry which we presume can meet the national consumption needs. Fourth, to save our reserve that is used to import sugar and to protect domestic sugar industry in the unhealthylunfair glohal competition. The purpose of this study is to reveal and to measure the possibility of the government self sufficiency program to success by examining the relationship of production capacity, consumption level, sugar import level.